THE MEANING OF SUNDA CULTURAL CONSTRUCTION FOR JAVANESE INDIVIDUALS IN BANDUNG - Susanti, Santi; Sukaesih, Sukaesih (Universitas Padjadjaran, 2024)
The aim of this study was to investigate how Javanese individuals in Bandung perceive and apply the Sundanese culture, otherwise known as Kasundaan. We utilized a qualitative research approach, employing phenomenology, and interviewed seven Javanese informants with Kasundaan experience in their daily lives. Our data collection methods included interviews, observations, documentation, and literature studies. This study revealed that there was an extrinsic and Intrinsic Motivating Aspects as well as aspects of hope that motivated Javanese individuals in applying Kasundaan. Family environment, social environment, and the natural environment played a very big role in the formation of the meaning of Kasundaan on the Javanese and Chinese individual subjects of this research through their cultural literary experience in their lives. Being a Sundanese, for the research subjects was interpreted philosophically as a perspective and “nyunda” mindset and manifested in the form of a real contribution to the Sunda. This interpretation gives rise to self meaning of the Javanese individual in being a Sundanese, namely the self that explores Sundanese cultural knowledge and the self as a preserver of Sundanese culture.